Septal Thickness Does Not Impact Outcome After Hypertrophic Obstructive Cardiomyopathy Surgery (Septal Myectomy and Subvalvular Mitral Apparatus Remodeling): A 15-Years of Experience - Raffa, Giuseppe M.; Franca, Eluisa La; Lachina, Carlo; Palmeri, Andrea; Kowalewski, Mariusz; Lebowitz, Steven; Ricasoli, Alessandro; Greco, Matteo; Sciacca, Sergio; Turrisi, Marco; Morsolini, Marco; Stringi, Vincenzo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The aim of this study was to assess the impact of septal thickness on long-term outcomes of surgical treatment for hypertrophic obstructive cardiomyopathy (HOCM) and correction of mitral subvalvular anomalies. Methods Sixty-six consecutive patients (58 ± 12 years, 56% female) undergoing extended septal myectomy and subvalvular mitral apparatus remodeling from 2007 to 2021 were retrospectively reviewed. Patients were divided into 2 groups according to septal thickness: moderate [< 18 mm, 29 patients (44%)] and severe [≥ 18 mm, 37 patients (56%)]. End points included survival, symptom improvement, reduction of left ventricle outflow tract (LVOT) gradient, resolution of mitral regurgitation (MR), and reoperation. Results The mean interventricular septal thickness was 19 ± 3 mm, 15.8 ± 0.8 mm in patients with moderate and 21.4 ± 3.2 mm in those with severe hypertrophy. Preoperative data, intraoperative variables, postoperative complication rates, pre-discharge echocardiographic and clinical parameters did not differ between the two study groups [except for procedures involving the posterior mitral leaflet (p = 0.033) and septal thickness after myectomy (p = 0.0001)]. Subvalvular apparatus remodeling (secondary chordae of mitral valve resection and papillary muscle and muscularis trabecula procedures including resection, splitting, and elongation) was invariably added to septal myectomy (100%). Four (6%) procedures involved the posterior mitral leaflets. Mitral valve replacement was carried out in two patients (3%, p = 0.4). Reoperation for persistent MR was necessary in one patient (1%, p = 0.4). Neither iatrogenic ventricular septal defect nor in-hospital mortality occurred. During follow-up (mean 4.8 ± 3.8 years), two deaths occurred. NYHA class was reduced from 2.9 ± 0.7 to 1.6 ± 0.6 (p < 0.0001), the LVOT gradient from 89.7 ± 34.5 to 16.3 ± 8.8 mmHg (p < 0.0001), mitral valve regurgitation grade from 2.5 ± 1 to 1.2 ± 0.5 (p < 0.0001), and septal thickness from 18.9 ± 3.7 to 13.9 ± 2.7 mm (p < 0.0001). Conclusions Regardless of septal thickness, subvalvular apparatus remodeling with concomitant septal myectomy can provide satisfactory long-term outcomes in terms of symptom improvement, LVOT obstruction relief, and MR resolution (without mitral valve replacement in most cases) in patients with HOCM.